2022
DOI: 10.5713/ab.21.0476
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate attenuates lipopolysaccharide induced intestinal barrier injury by regulating corticotropin-releasing factor pathway in weaned pigs

Abstract: Objective:The purpose of this study was to evaluate the protection of glutamate (GLU) against the impairment in intestinal barrier function induced by lipopolysaccharide (LPS) stress in weaned pigs.Methods: Twenty-four weaned pigs were divided into four treatments containing: 1) non-challenged control, 2) LPS-challenged control, 3) LPS+1.0% GLU, and 4) LPS+2.0% GLU.On day 28, pigs were treated with LPS or saline. Blood samples were collected at 0, 2 and 4 h post-injection. After blood samples collection at 4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Glutamate has been reported to be elevated in the plasma of active CeD patients (53). It has been also shown to enhance intestinal barrier integrity and antioxidant functions, and to help reduce injury to the intestine caused by inflammation (56).…”
Section: Resultsmentioning
confidence: 99%
“…Glutamate has been reported to be elevated in the plasma of active CeD patients (53). It has been also shown to enhance intestinal barrier integrity and antioxidant functions, and to help reduce injury to the intestine caused by inflammation (56).…”
Section: Resultsmentioning
confidence: 99%
“…Proinflammatory and regulatory mediators are released along with MC activation, and many of them have an effect on the intestinal barrier as well as modulating immune response [ 5 , 22 ]. With zona occludens 1 protein (ZO-1) as an indicator of the intercellular TJ between intestinal epithelial cells, we observed that TJ was markedly damaged on Caco2 cells by the culture medium of HMC-1 pre-treated with CRH, and JM25-1 restored the TJ ( Figure 3 A,D,E).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that LPS can disrupt intestinal barrier integrity and reduce intestinal tight junction mRNA expression and protein levels [5,33]. Wang H et al found that the expression level of CLDN-1 mRNA in the jejunal mucosa was signi cantly down-regulated4 h after intraperitoneal injection of 100 µg/kg BW LPS in weaned piglets, while the mRNA expression level of OCLN was not signi cantly affected [34].…”
Section: Discussionmentioning
confidence: 99%
“…Intactness of intestinal barrier function is pivotal for the growth performance, health and welfare of animals. Numerous scienti c evidences showed that bacterial infection, endotoxin challenge can impair barrier function and integrity of the small intestine in animals [4,5]. In fact, nursery piglets with immature gut are commonly subjected to weaning stress resulting physiological, environmental, and social stressors in the modern swine farm [6].…”
Section: Introductionmentioning
confidence: 99%